Clinical Risk Factors Associated with Kidney Stones in Adult Patients at Tarakan Regional General Hospital - Putri, Mega Indira Rajan; Kumar, Bhanu; Pandapotan, Roy Akur; Arsita, Elli (Jurnal MedScientiae, 2026)
Kidney stones are a common health probem that can cause various complications. Various clinical factors are thought to play a role in the occurrence of kidney stones, particularly metabolic conditions and urinary tract disorders. This study aims to analyze the relationship between diabetes mellitus, hypertension, obesity, urinary tract infections, and urinary tract obstruction with the occurrence of kidney stones in adult patients. This study is an analytical observational study with a cross-sectional design using medical record data of adult patients at Tarakan Central Hospital in Central Jakarta. Data analysis was performed univariately, bivariately using the Chi-Square test, and multivariately using binary logistic regression. The results of the analysis showed that hypertension and diabetes mellitus were significantly associated with the occurrence of kidney stones. Hypertension was the most dominant factor with an odds ratio (OR) of 3.924 (95% CI: 1.249–12.330), while diabetes mellitus had an OR of 3.860 (95% CI: 1.259–11.850). Obesity and urinary tract infection did not show a statistically significant association. It can be concluded that hypertension and diabetes mellitus are risk factors associated with kidney stones in adult patients, with hypertension being the dominant factor.